Ethnic Diversity and Federation of Pakistan: A Societal Perspective - Tariq Anwar Khan (IDEA PUBLISHERS, 2020)
This paper aims to identify the factors responsible for reluctance of centre to decentralise power and imitation of the same trend in provinces while dealing with minority ethno-lingual identities. The paper explores questions: what is the nature of federalism in Pakistan? How federal question is dealt in the three constitutions of the republic? How differently ethnic groups responded to various federal arrangements orchestrated by the managers of the state over the years? Objectives of the study are to develop an understanding into the challenges posed to federalism in Pakistan and to develop a more inclusive approach for addressing the federal question. The discussion generated in this study is based upon qualitative analysis of existing published literature in the form of books, research articles, reports, and official documents. The narrative upon which the federation of Pakistan has been constructed is self-contradictory. The paper not only exposes the contradictions of this narrative but also includes societal perspective on the ethnic diversity and federation of Pakistan. It has been concluded that the crisis generated by over-centralisation of the state could only be resolved by ensuring the fundamental federal values like decentralization, provincial autonomy, and devolution within the provinces to the grass root level.